Monoclonal antibodies targeting type 2 inflammation in eosinophil-associated diseases during pregnancy: insights from two eosinophilic granulomatosis with polyangiitis cases and a comprehensive literature review - Davanzo, Federica; Iorio, Luca; Calligaro, Antonia; Doria, Andrea; Padoan, Roberto (Frontiers in Lupus, 2024)
Background With the widespread availability of monoclonal antibodies targeting type 2 inflammation, managing pregnancies in patients with eosinophil-associated diseases, including eosinophilic granulomatosis with polyangiitis (EGPA), has become a crucial issue. Methods Starting from a two-case series of patients with EGPA, safely treated with anti-interleukin (IL)5/IL5R monoclonal antibodies during pregnancy, we conducted a comprehensive literature review to identify cases reporting the use of monoclonal antibodies for treating EGPA and other eosinophil-associated diseases in pregnant women. Results We present two cases of patients with ANCA-negative EGPA. The first case involves a 35-year-old patient with benralizumab, resulting in successful disease control and a healthy pregnancy despite a history of miscarriage and gestational diabetes. The second case describes a 35-year-old woman who continued mepolizumab during pregnancy, leading to a healthy infant despite two prior early miscarriages. A literature review of 22 papers, covering 97 patients using biologics during pregnancy found no reports specific to EGPA but documented safe outcomes with monoclonal antibodies like mepolizumab, benralizumab, and dupilumab in other eosinophil-associated disorders. These biologics were effective in managing symptoms and reducing the need for oral glucocorticoids, with no observed teratogenic effects. However, complications such as gestational diabetes and preterm births were noted, particularly with dupilumab. No adverse events or pregnancy complications directly attributable to the biological therapy were reported. Conclusions Uncontrolled disease during pregnancy significantly threatens pregnancy viability, while the use of monoclonal antibodies effectively manages maternal disease, reduces glucocorticoid use, and helps prevent complications, even though more data are needed to establish risks and benefits.